Current understanding on pathogenesis and effective treatment of glycogen storage disease type Ib with empagliflozin: new insights coming from diabetes for its potential implications in other metabolic disorders - Maiorana, Arianna; Tagliaferri, Francesco; Dionisi-Vici, Carlo (Frontiers in Endocrinology, 2023)
Glycogen storage type Ib (GSDIb) is a rare inborn error of metabolism caused by glucose-6-phosphate transporter (G6PT, SLC37A4) deficiency. G6PT defect results in excessive accumulation of glycogen and fat in the liver, kidney, and intestinal mucosa and into both glycogenolysis and gluconeogenesis impairment. Clinical features include hepatomegaly, hypoglycemia, lactic acidemia, hyperuricemia, hyperlipidemia, and growth retardation. Long-term complications are liver adenoma, hepatocarcinoma, nephropathy and osteoporosis. The hallmark of GSDIb is neutropenia, with impaired neutrophil function, recurrent infections and inflammatory bowel disease. Alongside classical nutritional therapy with carbohydrates supplementation and immunological therapy with granulocyte colony-stimulating factor, the emerging role of 1,5-anhydroglucitol in the pathogenesis of neutrophil dysfunction led to repurpose empagliflozin, an inhibitor of the renal glucose transporter SGLT2: the current literature of its off-label use in GSDIb patients reports beneficial effects on neutrophil dysfunction and its clinical consequences. Surprisingly, this glucose-lowering drug ameliorated the glycemic and metabolic control in GSDIb patients. Furthermore, numerous studies from big cohorts of type 2 diabetes patients, showed the efficacy of empagliflozin in reducing the cardiovascular risk, the progression of kidney disease, the NAFLD and the metabolic syndrome. Beneficial effects have also been described on peripheral neuropathy in a prediabetic rat model. Increasing evidences highlight the role of empagliflozin in regulating the cellular energy sensors SIRT1/AMPK and Akt/mTOR, which leads to improvement of mitochondrial structure and function, stimulation of autophagy, decrease of oxidative stress and suppression of inflammation. Modulation of these pathways shift the oxidative metabolism from carbohydrates to lipids oxidation and results crucial in reducing insulin levels, insulin resistance, glucotoxicity and lipotoxicity. For its pleiotropic effects, empagliflozin appears to be a good candidate for drug repurposing also in other metabolic diseases presenting with hypoglycemia, organ damage, mitochondrial dysfunction and defective autophagy.